Protection of Alfalfa from salt stress using Endophytic bacteria - Berkai, Rania; Berrabah, Fathi, Directeur de thèse; Rezzoug, Asma, Directeur de thèse (Laghouat : Université Amar Telidji - Département de biologie, 2024)
Endophytes are microorganisms mostly bacteria present asymptomatically in plants and can exercise several beneficial activities for their hosts. There are many reports currently that microorganisms isolated from the extreme environments have great biotechnological applications in medicine, agriculture, and industry. Alfalfa is a fodder legume of great S116) were studied for their ability to reduce Medicago sativa salt stress. Results show different levels in responses of M. sativa alfalfa. Genomic analyses were performed using selectedeconomic importance, but its productivity is often affected by salt stress in arid and semi-arid regions. Endophytic bacteria, which colonize the internal tissues of plants in a symbiotic manner, represent a promising solution for improving the salt tolerance of alfalfa. To improve alfalfa salt stress resistance, four endophytic bacteria (M17, M50, S113 and strains M17 that show a good protection from salt stress. M17 is identified as Pseudomonas aeruginosastrain, Comparative genomic for both strains is illustrated. For Pseudomonas strains (M17): two strains associated with plants and two non-associated with plant, one phytopathogens and Human pathogen). The results shows 521 common genes and synteny analyses revelas a high conservation between the bacteria associated with plants. Pseudomonas which indicate a mechanism to protect plants from salt and other abiotic and biotic stresses.